Imaging lipid rafts reveals the principle of ApoE4-induced Aβ upregulation in human neurons - Se-In Lee; Heejin Lim; Na Yeon Kim; Jichang Yu; Joonho Cho; Hyein Lee; Dae Won Moon; Jinsoo Seo (iScience)
Summary: Lipid rafts in plasma membranes are thought to provide a platform for regulating signaling pathways by increasing the expression or proximity of proteins in the same pathway. Despite this understanding, the absence of direct, simultaneous observations of lipid rafts and their affiliated proteins has hindered a comprehensive assessment of their roles across various biological contexts. Amyloid-β (Aβ), a hallmark of Alzheimer’s disease (AD), is generated from the sequential cleavage of amyloid precursor proteins (APPs) by β- and γ-secretases, primarily within endosomes after APP endocytosis by canonical clathrin-mediated endocytosis in neurons. In this study, we developed a protocol for imaging APP on lipid rafts using time-of-flight secondary ion mass spectrometry (ToF-SIMS) and found that astrocyte ApoE4 contributes to an increase in APP localization on lipid rafts, subsequently elevating Aβ42 synthesis in a clathrin-independent manner in neurons.